The familiarity of parents-teenagers and depressed high school adolescents in the city of Yogyakarta - Febriani Emilda; Carla Machira; Abdul Wahab (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Familiarity of teens-parents and high school teenagers with incidence of depression in Yogyakarta CityPurposeThis study aimed to determine the differences in the incidence of depression in high school teenagers who are familiar and not familiar with their parents in Yogyakarta City.MethodsThis research was a cross-sectional study, involving 200 high school teenagers in Yogyakarta city and conducted in five high schools in Yogyakarta city. The independent variable was familiarity of parent-teens, the dependent variable was teenager depression and external variables were gender, parental employment status, and socioeconomic status. Data analysis included univariable, and bivariable analysis with Chi-square tests, to determine the strength of the relationship between independent and dependent variable and multivariable analysis with logistic regression tests.ResultsBivariable analysis showed a significant correlation between familiarity of parent-teens with teenagers’ depression. Teenagers who were not familiar with their parents were potentially 3.7 times more likely to get depressed than teenagers who were familiar with their parents. Multivariable analysis showed that there was a significant relationship between parental familiarity with teenagers’ depression when controlled for the variable of gender. Teenagers who are not familiar with their parents and female gender have 7.6 times greater potential to become depressed than teenagers who are familiar with their parents and male gender.ConclusionThe incidence of depression in high school teenagers who are not familiar with their parents was higher than teenagers who are familiar with their parents.